Microbiological Quality of Packaged Tea Beverages Using the 3M Petrifilm Rapid E. coli/Coliform Count Plate - Kurniati, Eka; Cahyo, Fandi Tri Fajar; Romadona, Fitria (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
Tea is a complementary drink which is currently being served in variety ways and can be found in many places. The form of packaging is also very diverse. Glass bottles, plastic bottles, metal cans, paper cups, and plastic cups are just few of the many different forms of packaging that are available. The Indonesian National Standards Agency has established several requirements that bottled drinking water must fulfill in order to be legally sold in the country; one of these requirements is that it cannot contain any bacteria that could potentially cause disease. However, the reality is that within the community there are still packaged drinks that are not safe for human consumption. This study tested the quality of bottled tea supplied in a university canteen using 10 brands in varying packaging. 3M Petrifilm Rapid E. coli/Coliform Count Plate is utilized. The test results showed that 10 brands of tea packaging that were sold negatively did not contain E.coli and Coliform, which could be seen by the lack of gas bubbles and discoloration on the petrifilm media. This means that all packaged beverage samples sold are safe to drink.